Two Glycosyltransferase Genes of Haemophilus parasuis SC096 Implicated in Lipooligosaccharide Biosynthesis, Serum Resistance, Adherence, and Invasion - Zhou, Qi; Feng, Saixiang; Zhang, Jianmin; Jia, Aiqing; Yang, Kaijie; Xing, Kaixiang; Liao, Ming; Fan, Huiying (Frontiers in Cellular and Infection Microbiology, 2016)
Haemophilus parasuis is a common opportunistic pathogen known for its ability to colonize healthy piglets and causes Glässer’s disease. The lipooligosaccharide (LOS) of H. parasuis is a potential virulence-associated factor. In this study, two putative glycosyltransferases that might be involved in LOS synthesis in H. parasuis SC096 were identified (lgtB and lex-1). Mutants were constructed to investigate the roles of the lgtB and lex-1 genes. The LOS from the ΔlgtB or Δlex-1 mutant showed truncated structure on silver-stained SDS-PAGE gel compared to the wild-type strain. The ΔlgtB and Δlex-1 mutants were significantly more sensitive to 50% porcine serum, displaying 15.0% and 54.46% survival rates, respectively. Complementation of the lex-1 mutant restored the serum-resistant phenotype. Additionally, the ΔlgtB and Δlex-1 strains showed impaired ability to adhere to and invade porcine kidney epithelial cells (PK-15). The above results suggested that the lgtB and lex-1 genes of the H. parasuis SC096 strain participated in LOS synthesis and were involved in serum resistance, adhesion and invasion.